Dune reconstruction and revegetation as a potential measure to decrease coastal erosion and flooding under extreme storm conditions. (15th April 2020) - Fernández-Montblanc, T.; Duo, E.; Ciavola, P.
Abstract: The high water level and extreme waves that occur during a storm may threaten coastal landscapes, including densely populated zones that may also suffer from erosion, increasing the flooding magnitude and the total risk level. Climate change and future sea-level rise may result in an increased impact of storms due to the changes in the frequency and/or magnitude of the extremes of these water levels and/or waves. Coastal dunes and their associated vegetation communities act as a barrier to storm surges and wind waves, reducing flooding and coastal erosion. Therefore, nature-based solutions to protect coastal areas have gained attention in the last years. This contribution aims at evaluating the effectiveness of dune system rehabilitation as a Disaster Risk Reduction (DRR) measure under the current and future sea level scenarios at a rapidly eroding coastline in Bellocchio (Italy, Northern Adriatic Sea). The design of the dune reconstruction and revegetation was performed according to the morphodynamics and ecosystem characteristics of the current dune system. The effectiveness of the DRR was assessed based on numerical tests. The hydro-morphodynamic model XBeach reproduced morphological changes and inundation caused by a recent extreme event. The proposed DRR results in an increase of 22% of the sediment budget of the dune-beach system under the current sea level, and of the 57% and 82% under future sea level rise, for low and high hazard scenarios, respectively. The maximum water volume of the flooding is reduced by 42% in the current sea level. The expected increase of maximum flooding water volume under future high hazard and low hazard scenarios is reduced of 25% and 59%, respectively. These benefits are discussed along with a simplified cost analysis. It is concluded that the complete rehabilitation (reconstruction and revegetation) of the dune system represents a proper Disaster Reduction Solution under current and future sea level rise scenarios. Graphical abstract: Image 1 Highlights: Numerical modelling of the role of dune vegetation on controlling storm impact. Dune rehabilitation was tested as a measure to reduce coastal flooding and erosion. An assessment of a nature-based solution to counteract sea level rise scenarios. Vegetation increases sediment budged of beach-dune system under overwash conditions. Reduction of the flooding extension and magnitude by dune system reconstruction.